Need Analysis of English Ebook Based on Merdeka Curriculum for Indonesian Senior High School Students - Nur Azmi Rohimajaya; Rudi Hartono; Issy Yuliasri; Sri Wuli Fitriati (Universitas Negeri Semarang, 2022)
This study intended to find out teachers’ and students’ problems, needs, and wants in developing an English ebook based on the Merdeka curriculum for Indonesian Senior High School. The method used in this study is the Research and Development (R & D) method with the ADDIE model. It has five stages: analyzing the needs, designing the material and media, developing the product, implementing the product, and evaluating the product. The study focuses on the need analysis stage. The subjects used in the study are tenth-grade of Senior High School teachers in Pandeglang, Banten that applied the Merdeka curriculum. The data collecting technique in the study were interviews and document analysis. The instruments used are an interview guide and an analysis sheet. The data were analyzed and described qualitatively. The finding showed that the current English coursebook does not reflect the Merdeka curriculum. The teachers and the students need an English ebook which simple and suitable for learning English. Therefore, the findings serve as the foundation to develop an English ebook based on the Merdeka curriculum for Indonesian Senior High School students.